Treinamento de provadores na análise sensorial de cafés especiais e avaliação das papilas gustativas - Blanco, Dayana Alejandra Orozco (2020)
Sensory analysis is important in the production chain of specialty coffees due to the fact that the tasters are responsible for obtaining the results of the sensory profiles. The sensory characteristics of coffee can add value to the product, which makes a specific coffee different from that of commodity coffees. During the cup tasting one must understand which factors interfere with the taster's perception so that they are monitored and / or controlled. Sensory analysis also interferes with the intrinsic factors of the taster, such asits anatomical characteristics. The taste buds are found in humans, in greater quantities on the tongue, being important in the perception of flavors. However, no studies were found in the literature to verify the relationship between the anatomy of the taste buds, as well as the performance of the taster in the cup tasting. Given this, the present study aimed to determine the relationship between the anatomy of the taste buds and the performance of a sensory panel of young people during training and training with specialty coffees. In addition, the effectiveness of the methodology applied to the training of these young people was verified. The methodology applied for the training was carried out for 10 people, with discriminative and descriptive tests for samples of non-special coffee, special coffee, basic flavors and basic aromas. The sensory analysis methodology for specialty coffees was also applied according to the Specialty Coffee Association SCA protocol. 4 images of the tasters' tongue were taken over 20 days. Then, they were processed to obtain the count, area and size of papillae data. The results obtained by the sensory panel in training the senses of smell, sight and taste was greater than 90% at the end of the training. The result of the initial cup test showed that 20% of the panel has no statistical differences in the cup test. In the final test, 70% showed no statistically significant differences. A possible relationship was observed between the performance of the tasters and the papillae area. It was concluded that the methodology used for the training and qualification of the youth sensorial panel was promising and, according to the results, it can be inferred that the area and number of taste buds have a relationship with the taster's performance during the analysis in this study.